Old and New from Multifrequency Astrophysics - Franco Giovannelli; Lola Sabau-Graziati (Acta Polytechnica CTU Proceedings, 2014)
In this short review paper we comment on some the most important steps that have been made in the past decades for a better understanding of the physics governing our Universe. The results we discuss come from the many groundand-space-based experiments developed for measuring astrophysical sources in various energy bands. These experimental results are discussed within the framework of current theoretical models. Because of the limited length of this paper, we have selected only a few topics that, in our opinion, have been crucial for the progress of our understanding of the physics of cosmic sources.